Nanoparticles for intravascular applications: physicochemical characterization and cytotoxicity testing - Matuszak, Jasmin; Baumgartner, Jens; Zaloga, Jan; Juenet, Maya; Da Silva, Acarilia Eduardo; Franke, Danielle; Almer, Gunter; Texier, Isabelle; Faivre, Damien; Metselaar, Josbert M.; Navarro, Fabrice P.; Chauvierre, Cedric; et al. (Nanomedicine, 2016)
We report the physicochemical analysis of nanosystems intended for cardiovascular applications and their toxicological characterization in static and dynamic cell culture conditions.Size, polydispersity and ?-potential were determined in 10 nanoparticle systems including liposomes, lipid nanoparticles, polymeric and iron oxide nanoparticles. Nanoparticle effects on primary human endothelial cell viability were monitored using real-time cell analysis and live-cell microscopy in static conditions, and in a flow model of arterial bifurcations.The majority of tested nanosystems were well tolerated by endothelial cells up to the concentration of 100 ?g/ml in static, and up to 400 ?g/ml in dynamic conditions. Pilot experiments in a pig model showed that intravenous administration of liposomal nanoparticles did not evoke the hypersensitivity reaction. These findings are of importance for future clinical use of nanosystems intended for intravascular applications.
EVALuna2:20021